2002
DOI: 10.1177/07419325020230030501
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Issues and Practices in Secondary Special Education

Abstract: teaching experience and the use of teaching approaches, and the teachers' involvement in transition services. METHOD ParticipantsOne hundred ninety-nine (199) secondary special educators teaching Grades 7 through 12 in the state of Wisconsin were randomly selected to participate in this study from a list of all secondary special education teachers (N = 4,809) supplied by the Wisconsin Department of Public Instruction (WDPI). Teachers employed by the Department of Corrections or the Department of Health and Fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 27 publications
6
47
0
Order By: Relevance
“…Despite this need, Conderman and Katsiyannis (2002) found that 85% of secondary special education teachers emphasized mostly content instruction. The teachers responded that they believed that direct instruction, which is typically remedial in nature at the high school level, was more appropriate at the elementary rather than the secondary level.…”
Section: Downloaded By [Queensland University Of Technology] At 09:44mentioning
confidence: 90%
“…Despite this need, Conderman and Katsiyannis (2002) found that 85% of secondary special education teachers emphasized mostly content instruction. The teachers responded that they believed that direct instruction, which is typically remedial in nature at the high school level, was more appropriate at the elementary rather than the secondary level.…”
Section: Downloaded By [Queensland University Of Technology] At 09:44mentioning
confidence: 90%
“…Secondary teachers were trained to teach subjects; primary teachers were trained to teach children; and special education teachers were trained to teach children with disabilities (Van Reusen et al, 2001;Vinson, 2002). The goal of special educators in secondary schools was for students to achieve their potential by learning skills which would enable them to live and work as independently as possible in the community after their school years (Conderman & Katsiyannis, 2002).…”
Section: The Traditional Special Education Teachermentioning
confidence: 99%
“…In a review of university teaching practices, Risko et al (2008) found that providing explicit explanations and examples, demonstrations of practices, and opportunities for guided practice of teaching strategies in practicum settings with pupils seemed most useful. Concurrently, teachers across the career continuum note concern in the quality and quantity of their preparation to support academically struggling students (Conderman & Katsiyannis, 2002;McHatton & McCray, 2007). Greenleaf, Jimènez, and Roller (2002) found that few teachers in their study reported knowing ways to help students develop strategies or use them to help their comprehension.…”
mentioning
confidence: 96%